Development of Augmented Reality-Assisted Interactive Student’s Worksheet on The Topic of Molecular Shape - Harta, Johnsen; Bili, Filmonia Greslita (Universitas Negeri Surabaya, 2023)
Chemistry learning at SMA Negeri 1 Kalasan still uses conventional teaching materials. Teachers have never developed and used interactive LKPD. Molecular shape is one of the topics that is considered difficult, abstract, and challenging, so teaching materials are needed that can visualize the concept well, one of them through using Augmented Reality technology. This research aims to: (1) create product that fulfill the development feasibility criteria; and (2) find put the response of students to the product during trial. This study is Research and Development (R&D) that refers to the 3D development model, namely Define, Design, and Develop. The instruments used in this study were interview sheet, survey questionnaire, validation sheets, questions item in the product, and questionnaire for students' response to the product. A number of 10 students of X MIPA class were selected through purposive sampling technique as research sample. The research data obtained were analyzed descriptively. The results showed that: (1) product has fulfilled the criteria of being very feasible and very valid with average percentage of 87%, very effective with average score of 99 that also supported by the acquisition of average percentage of completeness of working on questions of 97%, very practical with average percentage of 93%; and (2) students' response to the product is very good. The average percentage of student’s responses per aspect item in the questionnaire was 92.81%. About 70% students stated that product is interesting and easy to understand.